Visual pedagogy and probiotics for hearing impaired children: A pilot study - Amrita Sujlana; Ruchika Goyal; Parampreet Pannu; Shireen Opal; Palki Bansal (Wolters Kluwer Medknow Publications, 2017)
Context: Oral health care for children with special needs remains largely unmet. It is important that we should focus on preventive strategies for special children to help curtail and prevent oral diseases. Aim: This study aimed to assess the effect of visual pedagogy and probiotic mouth rinse on the periodontal health of hearing impaired children. Materials and Methodology: The study cohort consisted of twenty children with hearing impairment (HI) and 20 age-matched healthy children. The gingival index (GI), plaque index (PI), and salivary pH for all children were assessed at baseline, 15 days after oral hygiene training using visual pedagogy, 15 days after probiotic mouth rinse introduction, and at the end of the test period, i.e., 2 months after discontinuing probiotics. Statistical Analysis: Comparison of means was carried out using the Student's t-test. Intragroup parameters were assessed using the one-way ANOVA, followed by the post hoc Scheffe test. Value for statistical significance was fixed at 0.05. Results: The GI and PI scores did not improve significantly after oral hygiene training in either of the two groups. The use of probiotic mouth rinse significantly reduced GI scores (<0.01) and PI scores (<0.01) and increased salivary pH above the critical pH in both groups. Conclusion: The use of visual pedagogy coupled with probiotic mouth rinsing may improve the periodontal status of children with HI and should be explored as a preventive procedure for children with special health-care needs.